2020
DOI: 10.1182/blood.2020006449
|View full text |Cite|
|
Sign up to set email alerts
|

Zanubrutinib for the treatment of patients with Waldenström macroglobulinemia: 3 years of follow-up

Abstract: Inhibitors of Bruton's tyrosine kinase (BTK) have established therapeutic activity in patients with Waldenström macroglobulinemia (WM). Zanubrutinib, a potent and selective BTK inhibitor, was evaluated in a phase 1/2 study in patients with WM who were either treatment-naïve (TN) or had relapsed/refractory (R/R) disease. Patients had disease requiring treatment per International Workshop on Waldenström Macroglobulinemia (IWWM) criteria. Treatment was oral zanubrutinib 160 mg twice daily (n=50) or 320 mg once da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 27 publications
3
95
2
1
Order By: Relevance
“…An oral dose of the 320-mg QD dosage regimen in addition to the 160-mg BID dose may provide patients and caregivers with additional dosing flexibility and the potential for increased drug adherence. Choosing the optimal schedule to promote adherence in patients (especially in elderly patients) is an important consideration, given that the median age in clinical studies of zanubrutinib is approximately 65 years [23]. The blue open circles reflect the observed events in zanubrutinib-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…An oral dose of the 320-mg QD dosage regimen in addition to the 160-mg BID dose may provide patients and caregivers with additional dosing flexibility and the potential for increased drug adherence. Choosing the optimal schedule to promote adherence in patients (especially in elderly patients) is an important consideration, given that the median age in clinical studies of zanubrutinib is approximately 65 years [23]. The blue open circles reflect the observed events in zanubrutinib-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, bleeding is still observed using acalabrutinib at variable frequencies, any-grade 26-58% and major bleeding 1-5% (Byrd et al, 2020b;Ghia et al, 2020;Owen et al, 2020;Sharman et al, 2020;Sun et al, 2020). This is also the case for zanubrutinib (Guo et al, 2019), where 4.4-66% of any-grade and 0.3-2.2% of major bleedings were observed in treated patients (Song et al, 2020;Tam et al, 2020a;Trotman et al, 2020;Xu et al, 2020). In addition, as mentioned, data from a cellular assay for TEC phosphorylation suggest that zanubrutinib is less prone to interfere with TEC as compared to ibrutinib (Guo et al, 2019).…”
Section: Increased Risk For Bleedings Under Btki Treatmentmentioning
confidence: 92%
“…Bleedings caused by ibrutinib cannot only be associated with inhibition of both BTK and TEC, since this AE has also been found after treatment with more selective BTKis, such as acalabrutinib and zanubrutinib ( Byrd et al, 2020b ; Ghia et al, 2020 ; Owen et al, 2020 ; Sharman et al, 2020 ; Song et al, 2020 ; Sun et al, 2020 ; Tam et al, 2020a ; Trotman et al, 2020 ; Xu et al, 2020 ). In vitro experiments in human platelets showed that acalabrutinib does not inhibit TEC ( Byrd et al, 2016 ; Nicolson et al, 2018 ), which would suggest a reduced number of cases with bleeding.…”
Section: Increased Risk For Bleedings Under Btki Treatmentmentioning
confidence: 99%
“…At a dose of 160 milligrams twice daily 77 patients achieved an overall response rate of 95.9% with a ≥ VGPR rate at 24 months of 43.8%. Three year progression‐free survival was 80.5% 143 . A randomized phase three trial of this drug versus ibrutinib failed to meet its primary endpoint of a significantly higher ≥VGPR rate.…”
Section: Managementmentioning
confidence: 99%
“…One patient developed myelodysplastic syndrome 6 months after bendamustine initiation (1.4%). 129 In an East German lymphoma Study group trial 293 patients received bendamustine plus rituximab. The overall response rate was 91.4% The 5-year survival is estimated to be 78%, two therapy related myeloid neoplasms were seen (0.7%).…”
Section: Novel Agent Based Therapymentioning
confidence: 99%